2020
DOI: 10.1111/jcpp.13233
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: The strength of the genetic overlap between ADHD and other psychiatric symptoms – a systematic review and meta‐analysis

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) frequently co-occurs with other psychiatric disorders. Twin studies have established that these co-occurrences are in part due to shared genetic risks. However, the strength of these genetic overlaps and the potential heterogeneity accounted for by type of psychiatric symptoms, age, and methods of assessment remain unclear. We conducted a systematic review to fill this gap. Methods: We searched PubMed, PsycINFO, Embase, and Web of Science until March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 47 publications
4
38
0
Order By: Relevance
“…The phenotypic correlations between ADHD and the neurodevelopmental, externalizing and internalizing subfactors were all strong, and were moderately-tostrongly influenced by genetic variation, in line with previous research (21,30,49,50).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The phenotypic correlations between ADHD and the neurodevelopmental, externalizing and internalizing subfactors were all strong, and were moderately-tostrongly influenced by genetic variation, in line with previous research (21,30,49,50).…”
Section: Discussionsupporting
confidence: 89%
“…The correlated factors model (RMSEA=0.006, CFI=0.974) revealed that the three neurodevelopmental, externalizing and internalizing subfactors were moderately-tostrongly intercorrelated (r=0.46-0.77), and were all significantly and strongly correlated with ADHD (r=0.67-0.75). The magnitude of correlations, along with the heritabilities and co-heritabilities of the subfactors and ADHD, were overall in line with previous research ( Figure S1) (11,21,24,27,35,49,50). The bifactor model (RMSEA=0.004, CFI=0.982) revealed very similar within-individual and betweensibling correlations of ADHD with the general and specific factors compared to the higher-order model ( Figure S2 & Table S13).…”
Section: Secondary Analysessupporting
confidence: 88%
“…The phenotypic correlations between ADHD and the neurodevelopmental, externalising and internalising subfactors were all strong, and were moderately to strongly influenced by genetic variation, in line with previous research. 8,16,32,33 After accounting for the general psychopathology factor, the correlation between ADHD and the neurodevelopmental-specific factor remained moderately strong, and was largely genetic in origin, suggesting substantial unique sharing of biological mechanisms between disorders. In contrast, the correlation between ADHD and the externalising-specific factor was much smaller and was largely explained by non-shared environmental effects.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] A recent meta-analysis of twin studies, however, suggested substantial genetic overlap between ADHD and not only neurodevelopmental disorders, but also externalising and internalising disorders (genetic correlations, 0.49-0.56). 8 These quantitative genetic findings have been paralleled by recent molecular genetic research, further suggesting similar magnitudes of genetic associations between ADHD and neurodevelopmental, externalising and internalising disorders. [9][10][11] The substantial degree of genetic overlap between psychiatric disorders demonstrates that genetic variants that contribute to risk for developing psychiatric disorders have highly pleiotropic effects, i.e.…”
mentioning
confidence: 82%
“…Hur (2015) presented a review of twin studies on hyperactivity/inattention and Conduct Problems, which showed moderate to high (0.17-0.68) phenotypic correlations, and high genetic correlations (0.43-1.0). Based on a systematic review, Andersson et al (2020) reported a genetic correlation between externalizing symptoms and ADHD of 0.49 (CI 0.37-0.61). These findings are consistent with the substantial genetic correlation between aggression and ADHD (rg = 1.00, SE = 0.07) that was estimated in a recent meta-analysis of genome-wide association studies of childhood aggression and ADHD (Ip et al 2019).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%